PENGARUH SUPPLY CHAIN MANAJEMEN, ORIENTASI KEWIRAUSAHAAN, DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING (Studi Kasus Umkm Industri Kreatif Rotan Kecamatan Rumbai) - Sipayung Hermawan David; ibrahim Restu; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Supply Chain Management,Entrepreneurship Orientation, and Product Innovation partially and simultaneously oncompetitive advantage. This research is a quantitative research conducted on 26 RattanHandicraft creative industries in Rumbai District. The primary data of this study weredata collected using a questionnaire with a Likert scale. The results of the data wereprocessed using SPSS 23 for further analysis descriptively, and multiple regressionanalysis to determine the results of the research. 26 samples were selected using theSaturated sample method (from 26 population businesses of Tassel rattan handicrafts).The results of this study indicate that Supply Chain Management has an effect on thecompetitive advantage of the rattan handicraft business in Rumbai District.Entrepreneurship orientation affects the competitive advantage of the rattan craftbusiness in Rumbai District. Product innovation affects the competitive advantage of therattan craft business in Rumbai District. Supply Chain Management, EntrepreneurshipOrientation, and Product Innovation simultaneously influence the competitive advantageof rattan in Rumbai District. So if the 3 variables increase at the same time, it will causecompetitive advantage to increase. Keywords: Supply Chain Management, Entrepreneurship Orientation, ProductInnovation, Competitive Advantage